Positive Body Image of Female Students: A Predictive Study of the Integrative Body Image Model - Urvelyte, Egle; Perminas, Aidas (European Scientific Journal, ESJ, 2021)
This paper focuses on testing hypothesized psychosocial predictors factors (general unconditional acceptance, body acceptance by others, body function appreciation) for positive body image among 812 female students aged between 18 and 35 years. Path analysis procedures contained in the Mplus Version 7 program were used to evaluate the positive body image model. The positive body image model indicated that greater perceived body acceptance by others was linked to greater body function appreciation which in turn was linked to higher positive body image. Perceived body image acceptance by others was directly related to higher positive body image. General unconditional acceptance did not lead to female students greater body function appreciation. The findings revealed some important positive body image predicting factors, and these results can be used to improve positive body image interventions.